2016
DOI: 10.1021/acs.oprd.6b00181
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Improvement of Organic Photoreaction Efficiency in the Flow Microreactor by the Slug Flow Condition Using Water

Abstract: A typical (Paterno-Buchi type) organic photoreaction is examined in flow microreactors. Compared to the results achieved for simple one-layer flow modes, slug flow conditions (with the unreactive reagent composed of organic solution and water) achieve higher efficiency (conversion and yield) irrespective of the light source, concentration, and solvent. Furthermore, remarkably high productivity is also observed when only 5% water is added as an unreactive reagent. This method is broadly applicable for achieving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…As can be seen in Figure 4, the variation found in our actinometric measurements is similar to the values obtained in the Paternò-Büchi photoreactions by Terao et al [4b] and Nakano et al [7] However, even if an exponential increase of conversion with the gas content is present also in the work of Telmesani et al, [6] the acceleration of the reaction observed by them is significantly higher. This could be due to the different physical properties of their solvent (ethyl acetate vs. toluene and hexane), smaller tube diameter (0.8 mm vs. 1 mm) and different light absorption properties of the employed reaction mixture.…”
Section: Influence Of Gas Fraction On Actinometer Conversionsupporting
confidence: 90%
See 3 more Smart Citations
“…As can be seen in Figure 4, the variation found in our actinometric measurements is similar to the values obtained in the Paternò-Büchi photoreactions by Terao et al [4b] and Nakano et al [7] However, even if an exponential increase of conversion with the gas content is present also in the work of Telmesani et al, [6] the acceleration of the reaction observed by them is significantly higher. This could be due to the different physical properties of their solvent (ethyl acetate vs. toluene and hexane), smaller tube diameter (0.8 mm vs. 1 mm) and different light absorption properties of the employed reaction mixture.…”
Section: Influence Of Gas Fraction On Actinometer Conversionsupporting
confidence: 90%
“…To calculate the photon flux per liquid volume and the optical pathlength from the chemical actinometric measurements we need to determine how long the liquid was Nakano et al [7] and Telmesani et al [6] illuminated when passing through the microreactor. This was realized using residence time distribution (RTD) experiments.…”
Section: Influence Of Gas Fraction On Actinometer Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further process intensification can be achieved through continuous flow reactors . Furthermore, several recent publications illustrate the benefits of advanced reactor concepts, e.g., packed‐bed‐, pneumatic nebulizer‐, slug flow, annular flow, vortex or luminescent solar concentrator reactors .…”
Section: Example 3 – Reaction Engineering Of Photochemical Processesmentioning
confidence: 99%